Multi-Frequency Precise Point Positioning using GPS and Galileo data with smoothed ionospheric corrections - Basile, Francesco; Moore, Terry; Hill, Chris; McGraw, Gary; Johnson, Andrew (2018)
The poor signal visibility and continuity associated with urban environments together with the slow convergence/reconvergence time of Precise Point Positioning (PPP), usually makes PPP unsuitable for land navigation in cities. However, results based on simulated open areas demonstrated that, once Galileo reaches final operational capability, PPP convergence time will be cut in a half using dual-constellation GPS/Galileo observations. Therefore, it might be possible to extend the applicability of PPP to land navigation in certain urban areas. Preliminary results, based on simulations, showed that GPS/Galileo PPP is possible where buildings are relatively short and satellites minimum visibility requirement is met for most of the time. In urban environments, signal discontinuity and reconvergence still represent the major problem for traditional PPP, which is based on the ionosphere-free combination of two-frequency pseudo-range and carrier phase. An alternative method to mitigate the ionosphere delay is proposed in order to ensure the best positioning performance from multi-frequency PPP. Instead of using the ionosphere-free combination, here low noise dual- or triple-frequency pseudo-range combinations are corrected with ionosphere delay information coming from federated carrier smoothing (Hatch) iono-estimation filters for each satellite. This method provides faster re- convergence time and ensures the best possible positioning performance from the Galileo Alternative BOC modulation in multi-frequency PPP. Indeed, even though Galileo E5 has small tracking noise and excellent multipath rejection, its PPP positioning performance is limited by the influence of E1 signal errors in the ionosphere-free combination, degrading the quality of the measurements.